The Impact of Financial Support to Firms During Crises: The Case of Covid Aid in the EU - Giulia Canzian; Elena Crivellaro; Tomaso Duso; Antonella Rita Ferrara; Alessandro Sasso; Stefano Verzillo (CESifo GmbH, 2025)
The Covid-19 pandemic caused a global economic crisis, leading governments to provide substantial State Aid to support firms. This paper examines the effectiveness of Covid-related financial support in Spain and Italy, focusing on its impact on firm recovery. Using a difference-in-differences (DiD) approach combined with propensity score weighting, it compares outcomes of similar firms receiving aid to those without. The results show significant benefits for micro-firms, including mitigated turnover declines and increased investments in both tangible and intangible assets. The findings highlight the critical role of government support in business survival and recovery, especially for SMEs, during the pandemic.
Keywords: D04; D22; L25; L52; P43; 330; state aid; aid effectiveness; temporary framework; Covid; firm growth; investment; difference-in-differences.